Silver Nanowire Networks: Silver Nanowires Network Film with Enhanced Crystallinity toward Mechano‐Electrically Sustainable Flexible‐Electrode (Adv. Mater. Technol. 1/2021). Issue 1 (5th January 2021) - Kim, Mi‐Jeong; Ko, Dong‐Su; Kim, Jung‐Hwa; Cho, Eun‐Hyoung; Yang, Dae Jin; Kwak, Chan; Sohn, Hiesang
Abstract : In article number 2000838, Mi‐Jeong Kim, Hiesang Sohn, and co‐workers present crystallized Ag nanowires film (c‐Ag NWs), prepared through solution annealing (70 °C) for flexible electronic devices. The c‐Ag NWs film shows excellent mechano‐electric stability (resistance change, Δ R /Δ R o : 45%) after 200 000 bending cycles under strain of 6.7%. Additionally, c‐Ag NWs based patterned electrode demonstrates the comparable electrical property (9.41 kΩ) to that of ITO‐based one (8.01 kΩ).